Universal Health Care and Informal Labor Markets : The Case of Thailand - Wagstaff, Adam; Manachotphong, Wanwiphang (World Bank, Washington, DC, 2012)
This paper explores the possibility that universal health coverage may inadvertently result in distorted labor market choices, with workers preferring informal employment over formal employment, leading to negative effects on investment and growth, as well as reduced protection against non-health risks and the income risks associated with ill health. It explores this hypothesis in the context of the Thai universal coverage scheme, which was rolled out in four waves over a 12-month period starting in April 2001. It identifies the effects of universal coverage through the staggered rollout, and gains statistical power by using no less than 68 consecutive labor force surveys, each containing an average of 62,000 respondents. The analysis finds that universal coverage appears to have encouraged employment especially among married women, to have reduced formal-sector employment among married men but not among other groups, and to have increased informal-sector employment especially among married women. The largest positive informal-sector employment effects are found in the agricultural sector.